Seroepidemiology of Coxiella burnetii Infection and its Frequency as a Cause of Community-Acquired Pneumonia in Canada - Thomas J Marrie; Emidio de Carolis; Canadian Community Acquired Pneumonia Investigators (Canadian Journal of Infectious Diseases)
The present study tested acute and convalescent serum samples from 788 patients hospitalized for community-acquired pneumonia in seven Canadian provinces for antibodies to Coxiella burnetii. One hundred nine patients (13.8%) had antibodies to this microorganism, and seven patients had acute Q fever. Serological evidence of infection with C burnetii was present in patients from all seven provinces. Three of the seven cases of acute Q fever were from Manitoba, suggesting that there may be unrecognized cases of Q fever in this province. In addition, a case of acute Q fever in Newfoundland, where there had previously been no reported cases, was noted, although subsequently, an outbreak of Q fever on goat farms has been reported.